2021
DOI: 10.3390/pr9112059
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Modeling of Ammonia Nitrogen Removal from High Strength Synthetic Wastewater Using Vacuum Thermal Stripping

Abstract: Waste streams with high ammonia nitrogen (NH3-N) concentrations are very commonly produced due to human intervention and often end up in waterbodies with effluent discharge. The removal of NH3-N from wastewater is therefore of utmost importance to alleviate water quality issues including eutrophication and fouling. In the present study, vacuum thermal stripping of NH3-N from high strength synthetic wastewater was conducted using a rotary evaporator and the process was optimized and modeled using response surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…They found that after 1.5 h, 21.3% of the ammonia remained in the dairy manure digestate [17], while in the present study, 16% of the ammonia remained in the pig slurry after two hours. High ammonium removal has been achieved using highstrength synthetic wastewater in a rotary evaporator, such as 97.84% at a temperature of 65.5 • C, 73.3 kPa vacuum pressure and 59.6 min of operation [15]. Later, the same authors found that when using digested liquid dairy manure at a higher temperature of 69.6 • C with a vacuum pressure of 43.5 kPa and treatment time of 87.65 min, the removal efficiency fell to 93.58% [23].…”
Section: Laboratory-scale Low-temperature Evaporation Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that after 1.5 h, 21.3% of the ammonia remained in the dairy manure digestate [17], while in the present study, 16% of the ammonia remained in the pig slurry after two hours. High ammonium removal has been achieved using highstrength synthetic wastewater in a rotary evaporator, such as 97.84% at a temperature of 65.5 • C, 73.3 kPa vacuum pressure and 59.6 min of operation [15]. Later, the same authors found that when using digested liquid dairy manure at a higher temperature of 69.6 • C with a vacuum pressure of 43.5 kPa and treatment time of 87.65 min, the removal efficiency fell to 93.58% [23].…”
Section: Laboratory-scale Low-temperature Evaporation Plantmentioning
confidence: 99%
“…Although it will depend on the substrate and reactor configuration, typical values of the parameters favouring air stripping are a pH of between 10.0 and 11.0 and a temperature of up to 80 • C [14]. However, increasing the temperature to favour ammonium conversion to ammonia is an energy-intensive step, and more efficient processes have been developed, such as low-temperature vacuum evaporation [15][16][17]. When a vacuum is applied to an enclosed reactor, boiling point temperature decreases to below normal, thus reducing energy costs due to a 56% decrease in energy demand when operating at 65 • C compared to 102 • C [17].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the limitations of conventional one-factor-at-a-time (OFAT) optimization approaches, response surface methodology (RSM) as a more accurate and robust optimization technique was first introduced in the middle of 20th century. Response Surface Methodology has several advantages over traditional OFAT optimization approaches, including multiple response optimization, reduced experimentation, improved understanding of the process interactions, and enhanced prediction accuracy [ 15 , 16 ]. Response Surface Methodology, as an optimization approach, therefore, not only helps to overcome the limitations of the OFAT optimization process but also shows superior performance when it is applied in different branches of science and engineering [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%